Economy, polity, and society British intellectual history, 1750-1950 - Collini, Stefan 1947-; Whatmore, Richard; Young, B. W. (Cambridge University Press, 2000)
Economy, Polity, and Society and its companion volume History, Religion, and Culture bring together major new essays on British intellectual history by many of the leading scholars of the period, continuing a mode of enquiry for which Donald Winch and John Burrow have been widely celebrated. This volume addresses aspects of the eighteenth-century attempt, particularly in the work of Adam Smith, to come to grips with the nature of 'commercial society' and its distinctive notions of the self, of political liberty, and of economic progress. It then explores the adaptations of and responses to the Enlightenment legacy in the work of such early nineteenth-century figures as Jeremy Bentham, Tom Paine and Maria Edgeworth. Finally, in discussions which range up to the middle of the twentieth century, the volume examines particularly telling examples of the conflict between economic thinking and moral values